(untitled) - Leibenstein, Harvey (New York, 1957)
The first three chapters, introductory in character, outline the nature of the problem, and set forth my modus operandi. The heart of the book, to be found in chapters 4 to 13, may be divided roughly into two parts. In the first of these, the state of economic backwardness is analyzed. The characteristics usually found in densely populated underdeveloped economies are examined, discussed, and, in part, explained. The broad aim here is to show that these characteristics are part of a pattern, that they are of a piece, so to speak, and that they generally help to reinforce each other.
Keywords: Economic development,Developing countries,Phát triển kinh tế,Các nước đang phát triển